Gender differences in body experience - a comparison of people with and without tattoos - Jabłońska, Klaudia; Kuc, Michał; Rogala, Maciej; Giżewska, Kamila; Łoś, Tomasz; Lorenc, Karol; Bielawska, Olga; Gulbicka, Marta (Journal of Education, Health and Sport, 2023)
Tattooing is a body modification practice that an increasing number of people, regardless of age, education or gender, are opting for. Previous quantitative research on the population of people with tattoos has mainly focused on differences in various personal characteristics, but has not focused on the bodily experience of people with tattoos. The aim of the present study was to examine differences in body image, body schema and body sense in people with and without tattoos. Two hundred and eleven people participated in the study, 108 of whom had at least one tattoo. Respondents completed a set of questionnaires: The Battery of Tests of The Body Self Representations and a demographic questionnaire. Our study showed that there were no significant differences in terms of mental body representations in people with and without tattoos. The main differences in terms of mental body representations were between men and women without tattoos. The present study suggests the need for a deeper understanding of the importance of tattoo for bodily experience.